Teenage perception on interior design of public libraries - Ismail, Nur Hanis Najwa (2019)
in a world where technology has taken over our daily activities, the public library is still the place for the community of all ages to look for books and references for formal or informal studies. public libraries are one of the successful spaces designed for people of all ages as they encourage visitors to behave and interact positively in the environment. thus, teenagers as library users who are at the verge of becoming adults, need a more positive environment around them to observe and learn. however, only a few studies on public libraries and teenage visitors have been conducted. one of the issues is the lack of space designed specifically for teenagers, and the too formal ambience for the group in the public library. the study determined the physical characteristics of interior design in public libraries that would significantly affect teenage behaviour by identifying their design preferences and perceptions. the research utilized a mixed method of quantitative and qualitative data collection to identify the interior design characteristics of public libraries in malaysia that affect teenage behaviour. case studies were conducted on three public libraries in selangor. data on the characteristics were collected through observation, photographs and annotated sketches. next, to verify teenage perception and preferences on the interior design characteristics of public libraries, online questionnaire survey forms were forwarded to teenage online groups using the snowball technique. 70 respondents answered the survey within the time allocated. in addition, semi structured interviews were conducted on 13 teenage visitors of public libraries through random sampling to further investigate their perceptions and preferences of public library interior design. finally, the third objective is to determine the relationship between interior design characteristics of public libraries in malaysia and teenage behaviour, and the data for the analysis were from the triangulation of the collected data. statistical methods were used to analyse quantitative data while qualitative data were analysed through content analysis by systematically evaluating the texts and answers in a table form. the main output of the research showed that all the characteristics listed, namely bright colours, natural day lighting, informal and interactive furniture arrangement and furnishings are imperative in designing a better public library for a better learning environment for teenagers as agreed by the respondents. the findings contribute to the possibility of future studies on the interior design of public libraries for teenagers specifically in malaysia. hence, this research hopefully provides insights on the needs of teenagers with regard to space in public libraries. this enables architects and expert designers to strike a clearer balance between creating functional and inspiring buildings with exciting architectural features and enjoyable internal design spaces for teenagers as well as users of all ages.